Rates of inappropriate antiretroviral prescription among injection drug users - Bonner Simon; Kerr Thomas; Hogg Robert S; Wood Evan; Strathdee Steffanie A; Palepu Anita; Montaner Julio SG (BMC, 2007)
Abstract Background Although the survival benefits of antiretroviral therapy (ART) for the treatment of HIV infection are well established, the clinical management of HIV disease continues to present major challenges. There are particular concerns regarding access to appropriate HIV treatment among HIV-infected injection drug users (IDU). Methods In a prospective cohort study of HIV-infected IDU in Vancouver, Canada, we examined initial ART regimens vis-à-vis the provincial government's therapeutic guidelines at the time ART was initiated. Briefly, there have been four sets of guidelines: Era 1 (1992 to November 1995; double-drug (dual NRTIs) ART for patients with a CD4 cell count of 350 or less); Era 2 (December 1995 to May 1996; double-drug therapy for patients with a CD4+ cell count of 500 or less); Era 3 (June 1996 to June 1997; triple-drug therapy (dual NRTIs with a PI or NNRTI) for patients who had a plasma viral load of > 100,000 HIV-1 RNA copies/mL; dual therapy with two NRTIs for those with a plasma viral load of 5,000 to 100,000 HIV-1 RNA copies/mL); Era 4 (since July 1997; universal use of triple drug therapy as first-line treatment). Results Between May 1996 and May 2003, 431 HIV-infected individuals were enrolled into the cohort. By May 31, 2003, 291 (67.5%) individuals had initiated ART. We noted instances of inappropriate antiretroviral prescription in each guideline era, with 9 (53%) in Era 1, 3 (12%) in Era 2, 22 (28%) in Era 3, and 23 (15%) in Era 4. Of the 57 subjects who received an inappropriate ART regimen initially, 14 never received the appropriate therapy; among the remaining 43, the median time to the initiation of a guideline-appropriate ART regimen was 12 months (inter-quartile range 5 - 20). Conclusion The present study identified measurable rates of guideline-inappropriate ART prescription for patients who were injection drug users. Rates were highest in the era of dual therapy, although high rates persisted into the triple-therapy era. As therapeutic guidelines continue to evolve, it is critical that mechanisms be put in place to ensure prescription of ART combinations for IDU that are consistent with current expert recommendations.